2007
DOI: 10.1159/000110645
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids in TNF-α and Ethanol Actions

Abstract: During marijuana and alcohol consumption as well as during inflammation the reproductive axis is inhibited, mainly through the inhibition of luteinizing hormone-releasing hormone release. In male rats, this inhibitory effect is mediated, at least in part, by the activation of hypothalamic cannabinoid type 1 receptors (CB1). During inflammation, this activation of the endocannabinoid system seems to be mediated by an increase in TNF-α production followed by anandamide augmentations, similarly the effect of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, TNF‐induced modulation of TTX‐insensitive Na + currents at the plasma membrane in DRG neurons following TNF receptor I activation seems to be secondary to an increase in p38 MAPK phosphorylation (37). In addition, TNFα can cause the release of proposed TRP agonists such as endocannabinoids that may be responsible for mediating some of the downstream actions of TNFα (40–42). In fact, it has been suggested that the TRPV1 antagonist SB‐366791 can act presynaptically on neurons terminating in the dorsal horn of the spinal cord to inhibit glutamatergic transmission, a response that is blocked by SB‐366791 after peripheral inflammation (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, TNF‐induced modulation of TTX‐insensitive Na + currents at the plasma membrane in DRG neurons following TNF receptor I activation seems to be secondary to an increase in p38 MAPK phosphorylation (37). In addition, TNFα can cause the release of proposed TRP agonists such as endocannabinoids that may be responsible for mediating some of the downstream actions of TNFα (40–42). In fact, it has been suggested that the TRPV1 antagonist SB‐366791 can act presynaptically on neurons terminating in the dorsal horn of the spinal cord to inhibit glutamatergic transmission, a response that is blocked by SB‐366791 after peripheral inflammation (43).…”
Section: Discussionmentioning
confidence: 99%
“…8 The tumor necrosis factor alpha (TNF-α) is a proinflammatory cytokine, i.e., its increase indicates an inflammation in the body. 9 Interleukin-10 (IL-10)…”
Section: Introductionmentioning
confidence: 99%
“…1 h after treatment. Kopach et al 24 , Prestifillipo et al 17 , and Rettori et al 42 each offered pharmacological evidence for CB2 receptor regulation of salivation. We have previously shown that several nominally selective CB2 agonists/antagonists (JWH15/AM630) also work well at CB1 receptors 43 .…”
Section: Discussionmentioning
confidence: 99%